Day/night Changes in the Dorsomedial Hypothalamus Firing Responses to Ghrelin are Modulated by High-fat Diet. (1st July 2022) - Palus-Chramiec, K.; Sanetra, A.M.; Lewandowski, M.H.
Highlights: There is a day/night pattern of spontaneous activity in the DMH. Sensitivity express a day/night pattern to ghrelin application in the DMH. This rhythm is disrupted by the short term HFD consumption. Prolonged HFD consumption deepens the disruption in the DMH network. Abstract: Dorsomedial hypothalamus (DMH) is a part of the feeding center involved in food intake and regulation of the metabolism. DMH neurons express many receptors for different metabolic cues which can modulate its network and influence animals' behaviour. One of the metabolic peptides delivered to this structure is ghrelin, the only well-known hunger signal, produced mainly in the stomach. Diet-induced obesity is a physiological model of obesity widely used in research. Here we investigated how time-of-day and high-fat diet (HFD) affect neuronal networks and the sensitivity to the metabolic information received by the DMH. Our results indicate that even a short period of HFD (2–3 weeks) consumption can cause dysregulation of the DMH neuronal network, manifested as a disruption of the day/night pattern of basal activity and altered sensitivity to incoming information. We showed for the first time a day/night pattern of sensitivity to ghrelin in the DMH, with a higher level during the behaviorally active phase of animals. This day/night rhythm of sensitivity to ghrelin was reversed in HFD group, causing a stronger effect during the non-active phase. After prolongation of the HFD consumption to 7–8 weeks we observed an increase in the responsiveness to ghrelin, than during the short-term diet.